Hypothyroidism and its Physiological Consequences in Pulmonary Functions - Sushil Kharel; Subash Pant; Sanat Chalise; Binod Raut (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Hypothyroidism is very common globally and there is exponential elevation in hypothyroidism in Nepal as well. There are very few studies done in past to assess effect of hypothyroidism on pulmonary function. This study was conducted to study pulmonary function test in hypothyroid patients and to evaluate and asses the pulmonary function with thyroid stimulating hormone levels in newly detected hypothyroid patients. Materials and Methods: A total of 51 (21 Male & 30 Female) hypothyroid patients were selected and equal number 51 (21 Male & 30 Female) of matched control groups were taken. Participants participated voluntarily after being given a detailed explanation of the purpose of the study. All newly detected hypothyroid patients visiting medicine OPD of KMCTH were included in the study. Smokers, former smokers, patients suffering from debilitating and pulmonary diseases were excluded from the study. Results: Pulmonary function tests were evaluated by computerized spirometer HELIOS 702. Data obtained was analyzed with the help of SPSS. Both FVC (Cases: 1.77 ± 0.35 & Controls: 2.85 ± 0.46) and FEV1 (Cases: 1.30 ± 0.35 & Controls: 2.38 ± 0.41) means were decreased in hypothyroid patients. Forced vital capacity (FVC) and forced expiratory volume in one sec (FEV1) showed strong negative correlation with Thyroid stimulating hormone levels (TSH). Conclusion: Hypothyroidism affects the pulmonary function to variable degree with higher levels of TSH. All hypothyroid patients must be assessed for abnormalities of pulmonary function to prevent from adverse outcomes.